Experimental investigation on the effect of phase change materials for thermal management improvement of the fast charging power module - Liu, Xianfei; Zhang, Zirui; Zhu, Caixia; Wang, Fang; Zhao, Doudou; Li, Zhiqiang; Liu, Yuhang; Zhang, Hui; Jiang, Hao (Case studies in thermal engineering, 2023)
This experimental research clarifies the advantageous effect of adding paraffin wax as the appropriate organic phase change material (PCM) to control the temperature rise of the fast charging power module (100 mm × 50 mm × 20 mm). The effects of PCM physical parameters (thermal conductivity, melting point temperature and filling thickness) on the thermal management performance of changing module are examined, and the PCM melting process is visualized to reveal the mechanism of PCM in improving the thermal management performance. Results show that the temperature is decreased by 46.4 °C with coupling the PCM, and a temperature reduction of 11.8 °C is found with increasing the air flow velocity. Increasing the PCM thermal conductivity from 0.2 W/(m∙K) to 5 W/(m∙K) in 1800 s can decrease the extreme temperature from 60.1 °C to 51.9 °C. The filling PCM thickness of 4.5 mm is more successful than other thicknesses in the thermal management performance. These research results will provide reliable technical solutions for improving the thermal management performance of charging piles and solving the effective thermal management of high-power quick charging piles.